Design and synthesis of a highly efficient labelling reagent for incorporation of tetrafluorinated aromatic azide into proteins. Issue 7 (15th February 2019) - Ma, Dejun; Kang, Xueying; Gao, Yasi; Zhu, Jiqin; Yi, Long; Xi, Zhen
Abstract: Chemical labelling can significantly extend the structures and functions of proteins for advanced applications. Herein, a highly efficient bench-stable reagentdiazo-azide was designed and synthesized for the incorporation of tetrafluorinated aromatic azides into proteins via the diazonium coupling. Thediazo-azide -labelled proteins could be further functionalized via the nonhydrolysis Staudinger reaction to achieve fluorescence labelling, PEGylation and biotinylation. The whole protein labelling processes were catalysis-free and could be finished within several hours under the mild conditions. To this end, we have prepared thickened viral nanoparticles with controllable diameters. Graphical abstract: